2020
DOI: 10.1590/0103-8478cr20200281
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a standard area diagram set to assess powdery mildew severity on watermelon leaves

Abstract: The development and validation of a standard area diagram set (SADs) was proposed in this study to assess the severity of powdery mildew (Podosphaera xanthii) in watermelon (Citrullus lanatus) leaves. The SADs proposed has twelve levels of severity, varying from 0.07 to 100%. The SADs were validated by 16 raters who had no previous experience in evaluating plant disease severity. Initially, the estimation of severity was performed without the use of the SADs in leaves with different levels of severity. In a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The severity of the damage caused by thrips to the peanut crop is usually evaluated subjectively by analyzing visually the caused symptoms (Moraes, 2005;Montes et al, 2013). Therefore, developing and validating a diagrammatic scale is useful to determine disease and pest intensity, which is important for different purposes including understanding yield loss, comparing cultivar behavior, and evaluating the effects of chemical and biological control (Bock et al, 2010;Boito et al, 2013;Vieira et al, 2014;Crenna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the damage caused by thrips to the peanut crop is usually evaluated subjectively by analyzing visually the caused symptoms (Moraes, 2005;Montes et al, 2013). Therefore, developing and validating a diagrammatic scale is useful to determine disease and pest intensity, which is important for different purposes including understanding yield loss, comparing cultivar behavior, and evaluating the effects of chemical and biological control (Bock et al, 2010;Boito et al, 2013;Vieira et al, 2014;Crenna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, linear regression continues to be used by some phytopathometrists for evaluating SADs (Santos et al 2017;Camara et al 2018;Trojan and Pria 2018;Arias et al 2020;Robaina et al 2020;Kublik et al 2020). The two linear regression coefficients (intercept and slope), together with the coefficient of determination (R 2 ), are usually reported for each rater in the SAD validation study, while those phytopathometrists reporting LCCC statistics have most often reported means of all raters combined (Del Ponte et al 2017;Bock et al 2020;Brás et al 2020;Nascimento et al 2020;Rivera et al 2020;Castellar et al 2021;Montero et al 2021).…”
Section: Introductionmentioning
confidence: 99%